From Oral Tradition To Digital Media: The Recontextualization Of Betawi Culture From Lotman’s Semiotic Perspective In The Works Of Tadjuddin Nur - Somadi Sosrohadi; Andi Fenty Bakti Anwar; Muhammad Syachrun Sjam; Fakhreny Fathu Rahman (Hasanuddin University, 2026)
This article examined the transformation of Betawi oral culture in the digital age through a semiotic analysis of the works of Tadjuddin Nur. Oral culture, which previously existed in the form of live performances, is now shifting to audio-visual digital platforms, such as YouTube. This study employed a semiotic approach by combining Charles Sanders Peirce’s triadic theory of signs and Yuri Lotman’s cultural semiotics perspective to understand how meaning is produced, represented, and reinterpreted in a digital context. Research methods included netnography and multimodal analysis of verbal, visual, and performative elements in Tadjuddin Nur’s YouTube content. The findings revealed that digitization functions as a space for recontextualization, generating new, more interactive, and multimodal forms of oral tradition, where Tadjuddin Nur acts as a cultural mediator bridging oral traditions with digital technology within a dynamic semiosphere. In addition, the study shows that digital media make Betawi oral traditions more accessible to a wider audience. At the same time, these platforms allow the culture to adapt and remain relevant in today’s modern society.